Determination Of Some Engineering, Pomological And Chemical Parameters Of The Wild Tomato (Solanum peruvianum and Solanum huaylasense) Genotypes To Be Used In Breeding Programs - KABAS, Onder; KABAS, Aylin (MAS Journal of Applied Sciences, 2022)
In this study, pomological, chemical and strength parameters of three different wild tomatogenotypes were determined and their potential use in further breeding programs was investigated.Experiments were conducted with Solanum peruvianum (LA2744, LA0462) and S. huaylasense (LA1982)in randomized blocks design with three replicates. Statistical analyses revealed that genotypes hadsignificant effects on pomological and chemical properties. For strength parameters, genotypes did not havesignificant effects on firmness and poison ratio, but had significant effects on the other strength parametersat 1% level. It was concluded based on present findings that LA1982 was prominent for pomologicalproperties, chemical and strength parameters and thus was considered as a significant gen source for furtherbreeding programs.